2021
DOI: 10.1101/2021.05.04.21256571
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fatal COVID-19 outcomes are associated with an antibody response targeting epitopes shared with endemic coronaviruses

Abstract: It is unclear whether prior endemic coronavirus infections affect COVID-19 severity. Here, we show that in cases of fatal COVID-19, antibody responses to the SARS-COV-2 spike are directed against epitopes shared with endemic beta-coronaviruses in the S2 subunit of the SARS-CoV-2 spike protein. This immune response is associated with the compromised production of a de novo SARS-CoV-2 spike response among individuals with fatal COVID-19 outcomes.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…It is unknown if the recall of β-hCoV antibodies upon SARS-CoV-2 infections impacts disease outcome. A recent study suggests that the recall of OC43 β-hCoV antibodies is associated with a compromised de novo SARS-CoV-2 response in individuals with fatal COVID-19 37 .…”
Section: Introductionmentioning
confidence: 99%
“…It is unknown if the recall of β-hCoV antibodies upon SARS-CoV-2 infections impacts disease outcome. A recent study suggests that the recall of OC43 β-hCoV antibodies is associated with a compromised de novo SARS-CoV-2 response in individuals with fatal COVID-19 37 .…”
Section: Introductionmentioning
confidence: 99%
“…The use of S1 as an immunogen has been proposed for other highly pathogenic coronaviruses, such as MERS-CoV and SARS-CoV, because of its potential high safety profile compared to the use of full-length S. Although full-length S protein can induce the highest immune response, some reports suggested its association with possible side effects in the currently used COVID-19 vaccines [22,23]. Additionally, previous reports on MERS-CoV, SARS-CoV and other coronaviruses have suggested that the use of a fulllength S based vaccine could lead to undesired immune response upon infection [24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these aforementioned vaccines rely on using either the full-length S protein or the RBD as the immunogen because of their critical roles in viral entry and host tropism [19,20], and ability to elicit protective immunity in animals and humans after vaccination or infection [9,10,21]. Use of fulllength S protein as immunogen, however, could be associated with undesired responses by inducing non-neutralizing antibodies which may contribute to disease enhancement, immunopathological inflammation and fatality [22][23][24][25][26][27][28]. As such, targeting the S1 subunit could help minimize a potentially undesirable effect.…”
Section: Introductionmentioning
confidence: 99%
“…The use of S1 as an immunogen has been proposed for other highly pathogenic coronaviruses such as MERS-CoV and SARS-CoV because its potential high safety profile compared to the use of full-length S. Although full-length S protein can induce the highest immune response, some reports suggest its association with possible side effects in the currently used COVID-19 vaccines [22,23]. Additionally, previous reports on MERS-CoV, SARS-CoV and other coronaviruses have suggested that the use of full-length S based vaccine could lead to undesired immune response upon infection [24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these aforementioned vaccines rely on using either the full-length S protein or the RBD as the immunogen because of their critical roles in viral entry and host tropism [19,20], and ability to elicit protective immunity in animals and humans after vaccination or infection [9,10,21]. Use of full-length S protein as immunogen, however, could be associated with undesired responses by inducing non-neutralizing antibodies which may contribute to disease enhancement, immunopathological inflammation and fatality [22][23][24][25][26][27][28]. As such, targeting the S1 subunit could help minimize potentially undesirable effect.…”
Section: Introductionmentioning
confidence: 99%